A computational study of 2D group-III ternary chalcogenide monolayer compounds MNTe2(M, N = In, Ga, Al) - Khengar, S J; Parmar, P R; Modi, Nidhi; Thakor, P B (Journal of physics. Condensed matter, 2023)
First principle calculations of novel two-dimensional (2D) group-III ternary chalcogenide monolayer (G3TCM) compounds have been carried out using density functional theory. The 2D hexagonal structure has a honeycomb-like appearance from both the top and bottom views. Both pristine and G3TCM compounds are energetically favourable and have been found to be dynamically stable via phonon calculations. Theab-initiomolecular dynamics calculations show the thermodynamical stability of the G3TCM compounds. The G3TCM compounds exhibit semiconductor behaviour with a decreased indirect bandgap compared to the pristine monolayers. Chalcogen atoms contribute mainly to the valence bands, while group-III atoms have a major contribution to the conduction band. A red shift has been observed in the absorption of light, mainly in the visible and ultraviolet regions, and the refractive index is increased compared to the pristine material. Both pristine and G3TCM compounds have been found to be more active in the ultraviolet region, and low reflection has been observed. In the 6-8 eV range of the ultraviolet region, zero reflection and the highest absorption are observed. The monolayer has shown potential applications in optoelectronics devices as an ultraviolet and visible light detector, absorber, coating material, and more. The band alignment of the 2D G3TCM monolayer is calculated to observe its photo-catalyst behaviour.First principle calculations of novel two-dimensional (2D) group-III ternary chalcogenide monolayer (G3TCM) compounds have been carried out using density functional theory. The 2D hexagonal structure has a honeycomb-like appearance from both the top and bottom views. Both pristine and G3TCM compounds are energetically favourable and have been found to be dynamically stable via phonon calculations. Theab-initiomolecular dynamics calculations show the thermodynamical stability of the G3TCM compounds. The G3TCM compounds exhibit semiconductor behaviour with a decreased indirect bandgap compared to the pristine monolayers. Chalcogen atoms contribute mainly to the valence bands, while group-III atoms have a major contribution to the conduction band. A red shift has been observed in the absorption of light, mainly in the visible and ultraviolet regions, and the refractive index is increased compared to the pristine material. Both pristine and G3TCM compounds have been found to be more active in the ultraviolet region, and low reflection has been observed. In the 6-8 eV range of the ultraviolet region, zero reflection and the highest absorption are observed. The monolayer has shown potential applications in optoelectronics devices as an ultraviolet and visible light detector, absorber, coating material, and more. The band alignment of the 2D G3TCM monolayer is calculated to observe its photo-catalyst behaviour.